2015 IEEE International Conference on Multimedia Big Data 2015
DOI: 10.1109/bigmm.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

Negative Bootstrapping for Weakly Supervised Target Detection in Remote Sensing Images

Abstract: When training a classifier in a traditional weakly supervised learning scheme, negative samples are obtained by randomly sampling. However, it may bring deterioration or fluctuation for the performance of the classifier during the iterative training process. Considering a classifier is inclined to misclassify negative examples which resemble positive ones, comprising these misclassified and informative negatives should be important for enhancing the effectiveness and robustness of the classifier. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The clear improvements obtained by subsequent methods show that the usage of more powerful feature extractors such as CNN allows fully supervised approaches to be outperformed based on handcrafted features (BOV [93] and FDDL [91]). The results are consistent with the literature stating that handcrafted features are not powerful enough to accurately describe objects in RSIs [31,33,34].…”
Section: Google Earth Datasetsupporting
confidence: 91%
See 2 more Smart Citations
“…The clear improvements obtained by subsequent methods show that the usage of more powerful feature extractors such as CNN allows fully supervised approaches to be outperformed based on handcrafted features (BOV [93] and FDDL [91]). The results are consistent with the literature stating that handcrafted features are not powerful enough to accurately describe objects in RSIs [31,33,34].…”
Section: Google Earth Datasetsupporting
confidence: 91%
“…Before the advent of deep learning (DL), most object detectors were based on SVMs. The workflow behind these methods is to start by producing candidate proposals exploiting either a Sliding Window (SW) [31,32,36] or Saliency-based Self-adaptive Segmentation (Sb-SaS) [29,30,33,34] approach. SW generates proposals by sliding, on the entire image, multiple BBs with different scales while Sb-SaS produces saliency maps that measure the uniqueness of each pixel in the image and exploit a multi-threshold segmentation mechanism to produce BBs.…”
Section: Tsi + Tdl-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most of geospatial object detection methods, except for few works such as (Han et al, 2015;Tang et al, 2015;Wang et al, 2015;Zhou et al, 2015b), are still dominated by handcrafted features and shallow learning-based features (e.g. SR-based features (Chen et al, 2011b, c;Cheng et al, 2014c;Du and Zhang, 2014;Han et al, 2014;Liu and Shi, 2014;Yokoya and Iwasaki, 2015;Zhang et al, 2014a;Zhang et al, 2015c;Zhang et al, 2015d)).…”
Section: Deep Learning-based Feature Representationmentioning
confidence: 99%
“…Although a few WSL approaches have been developed for natural scene image analysis (Deselaers et al, 2012;Zhu and Shao, 2014), those methods cannot be directly used for geospatial object detection because they are insufficient to address the challenges of RSIs, such as variations in the visual appearance of objects and complex background clutter. As an initial effort, our recent work in (Han et al, 2015;Zhang et al, 2015a;Zhou et al, 2015a;Zhou et al, 2015b) have shown the feasibility of using WSL for geospatial object detection. However, two challenging problems still exist.…”
Section: Weakly Supervised Learning-based Geospatial Object Detectionmentioning
confidence: 99%